Liberalizacija prometnega trga in preobrazba železnice - Zgonc, Bogdan (Promet - Traffic&Transportation, 2012)
In the process of transformation of the transport system in the EC the railway as a major technological_ system plays a significant role. This refers to Yugoslavia as well while it should be taken into account that some major structure changes happened, as shown through the comparison of the state in the 1960s and nowadays given in separate graphic presentations. The author advocates the requirement of an urgent harmonization of operations and development in the first place in the infrastructure because without respective harmonization and coordination it is not possible to reach the aspired-to liberalization.